2018
DOI: 10.7567/jjap.57.04fk06
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neuron operations and spike-timing-dependent plasticity using memristive devices for brain-inspired computing

Abstract: The use of memristive devices for creating artificial neurons is promising for brain-inspired computing from the viewpoints of computation architecture and learning protocol. We present an energy-efficient multiplier accumulator based on a memristive array architecture incorporating both analog and digital circuitries. The analog circuitry is used to full advantage for neural networks, as demonstrated by the spike-timingdependent plasticity (STDP) in fabricated AlO x /TiO x -based metal-oxide memristive device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
(41 reference statements)
1
2
0
Order By: Relevance
“…31,33,34) Variations such as process, supply voltage, and temperature (PVT) do not critically deteriorate the computation precision because of our differential signaling. It was also confirmed that the NN algorithm itself is inherently tolerant to variations of electrical parameters, 5,25,35) therefore, this motivates us to further involve emerging technologies after our prototyping in this study.…”
Section: Performance Evaluation and Discussionsupporting
confidence: 58%
“…31,33,34) Variations such as process, supply voltage, and temperature (PVT) do not critically deteriorate the computation precision because of our differential signaling. It was also confirmed that the NN algorithm itself is inherently tolerant to variations of electrical parameters, 5,25,35) therefore, this motivates us to further involve emerging technologies after our prototyping in this study.…”
Section: Performance Evaluation and Discussionsupporting
confidence: 58%
“…Controlling the resistances of a population of memristors in an analogue fashion, however, is not an easy task. Because of the uncontrollable variability, careful pulse tuning is required for each device to reproduce its designed behaviour 18 , hindering practical use of memristors for synaptic devices.…”
Section: Introductionmentioning
confidence: 99%
“…5,6) In order to meet the challenges posed by the above-mentioned problems, researchers are trying to find breakthroughs from multiple angles. As one of the solutions, brain-inspired computing, [7][8][9] such as artificial neural networks (ANNs), [9][10][11] is widely favored as a promising computing paradigm. [12][13][14] Deep neural networks (DNNs), one of the ANNs, are widely used in pattern recognition, language translation, visual object recognition, object detection, and many other fields.…”
Section: Introductionmentioning
confidence: 99%